Growth studies of Wheat varieties with application of organic fertilizers under Casuarina junghuhniana based agroforestry system - Shivam; Sandeep Arya; Chhavi Sirohi; Karishma Nanda; Ishu Redhu; G. B. Rawale; Visha Jain; Sumit (Indian Journal of Agroforestry, 2025)
A study was conducted at the research farm of the department of forestry, CCSHAU, Hisar, during Rabi 2022–2023 to evaluate the impact of organic fertilizers on the morphological growth parameters of wheat varieties grown under a Casuarina junghuhniana based agroforestry system planted at 5 × 3m spacing. Four wheat varieties (WH 1270, WH 1184, WH 1142, and WH 1124) were cultivated with three fertilizer treatments: T1 (recommended dose of nitrogen (RDN) through inorganic fertilizers), T2 (farmyard manure at 17.5 t/ha), and T3 (vermicompost at 8 t/ha). During the study period, tree height, girth and crown spread were increased by 5%, 5.8% and 5.1%, respectively. Plant population at 20 DAS was maximum in WH 1142 with T1 (RDN) under control conditions (369.3).With varying levels of organic fertilizer, the wheat crop in control conditions took fewer days to 50% flowering (91.9) and days to maturity (143.1) than the casuarina based agroforestry system. Treatment T1 (RDN) took the longest number of days to reach 50% flowering (100.7) and maturity (151.2) among all three treatments. Plant height and dry matter accumulation were also lower under the casuarina based agroforestry system compared to the control, with observations taken at 30-day intervals. These findings suggest that inorganic fertilizers may be more successful at enhancing wheat growth under casuarina based agroforestry system, but additional studies into long-term soil health and sustainable practices with organic fertilizers are needed.